Технико-экономические аспекты внедрения нового теплообменного оборудования - Хавина, Д. Г. (НТУ "ХПИ", 2011)
The new formulation for problem of plate heat exchangers design is presented. The criterion of reduced costs with taking into account leasing equipment is considered. The different variants of leasing made out. They must be insert in technical-economic problem of plate heat exchanger optimization.
Keywords: кожухотрубчатые теплообменники; пластинчатые теплообменники; финансовый лизинг; операционный лизинг